Komposisi dan Struktur Jenis Pohon pada Sistem Agroforestri Bambang Lanang di Empat Lawang, Sumatra Selatan: Tree Species Composition and Structure of Bambang Lanang Agroforestry System in Empat Lawang, South Sumatra - Lanuriati, Arisna; Sundawati, Leti; Hartoyo, Adisti Permatasari Putri (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Communities in Empat Lawang Regency, South Sumatra have implemented an agroforestry system. Bambang lanang (Magnolia champaca) is a local species and is mainly cultivated by the local communities in Empat Lawang Regency as a carpentry tree. However, the information of tree species composition and structure of Bambang lanang agroforestry system is still limited. This study aimed to analyze the tree species composition and structure in the Bambang lanang community forests. The method used was vegetation analysis in 4 villages with a total plot was 100 plots. The results showed that the agroforestry pattern was the most widely used pattern by Bambang lanang's farmers. The highest total plant species in the Bambang lanang community forest was found in Fajar Bakti Village (26 species). The highest number of species at the level of seedlings, saplings, poles, and trees in order were found in the villages of Muara Pinang (17 species), Paiker (17 species), Muara Pinang (12 species), and Paiker (20 species). The dominant plant species composition in the community forest is Bambang lanang, combined with Coffee (Coffea sp.), and Durian (Durio sp.). The agroforestry system contributes to the vegetation diversity. Keywords: complex agroforestry, Sumatra, vegetation analysis, vegetation diversity ABSTRAK Masyarakat di Kabupaten Empat Lawang, Sumatra Selatan telah mengimplementasi sebuah sistem agroforestry. Bambang lanang (Magnolia champaca) adalah jenis lokal dan umum dibudidayakan oleh masyarakat lokal di Kabupaten Empat Lawang sebagai kayu pertukangan. Oleh karenanya, informasi mengenai komposisi dan struktur jenis pohon pada sistem agroforestri Bambang lanang masih terbatas. Penelitian ini bertujuan untuk menganalisis komposisi dan struktur jenis pohon pada hutan masyarakat Bambang lanang. Metode yang digunakan adalah analisis vegetasi di 4 desa dengan total plot sebanyak 100 plot. Hasil penelitian menunjukkan pola agroforestri paling banyak digunakan oleh petani Bambang lanang. Jumlah spesies tertinggi ditemukan di hutan masyarakat Bambang lanang Desa Fajar Bakti (26 spesies). Jumlah spesies semai, pancang, tiang, dan pohon secara berurutan ditemukan di Desa Muara Pinang (17 spesies), Paiker (17 spesies), Muara Pinang (12 spesies), dan Paiker (20 spesies). Komposisi spesies tumbuhan dominan di hutan masyarakat adalah Bambang lanang yang dikombinasikan dengan kopi (Coffea sp.) dan durian (Durio sp.). Sistem agroforestri berkontribusi terhadap keanekaragaman vegetasi. Kata kunci: agroforestri kompleks, analisis vegetasi, keanekaragaman vegetasi, Sumatra